Interpreting fiscal accounting rules in the European Union. Issue 6 (17th June 2017) - Gandrud, Christopher; Hallerberg, Mark
ABSTRACT: In the European Union, the creation of public debt statistics starts with member state governments' reports. The EU's statistical agency – Eurostat – then revises. How do these actors' incentives shape reported numbers? Governments have incentives to take a more favourable view of often ambiguous accounting rules than Eurostat. Lower debt improves governments' performance with domestic and external audiences. Eurostat is tasked with monitoring budgets for 'excessive' debts. We expect governments to present debt figures that Eurostat then revises upwards. This is more likely when governments have high debts, especially when in the eurozone, and prior to elections. Financial crises heighten the number of policies needing interpretation and both actors have more incentives to shape the numbers. We examine these propositions using Eurostat's debt revisions. We find debts are revised upwards more for eurozone countries with higher debt levels and years with unscheduled elections. Financial stress strengthens these effects.